2023
DOI: 10.1371/journal.pone.0280060
|View full text |Cite
|
Sign up to set email alerts
|

The combined effect of pre-pregnancy body mass index and gestational weight gain on the risk of pre-labour and intrapartum caesarean section—The ICE-MCH study

Abstract: Women who are obese before pregnancy have a higher risk of caesarean section than normal weight women. We investigated the combined effect of pre-pregnancy weight and gestational weight gain on pre-labour and intrapartum caesarean section risk. We collected data on 22,763 singleton, term, live deliveries in 2003–2014 from the Icelandic Maternal and Child Health Study (ICE-MCH), based on Icelandic registries. These were the Icelandic Medical Birth Registry and the Saga Maternal and Child Health Database. Pre-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Maternal and child health are crucial determinants of a nation’s overall health and development. The impact of weight gain during pregnancy on short-term and long-term health outcomes underscores its significance in comprehensive pregnancy health management [ 1 , 2 , 3 , 4 ]. The findings, based on existing research evidence, suggested that excessive gestational weight gain (GWG) could lead to cesarean section, maternal weight retention, large-for-gestational-age (LGA) infants, gestational hypertension, preeclampsia, and gestational diabetes mellitus (GDM).…”
Section: Introductionmentioning
confidence: 99%
“…Maternal and child health are crucial determinants of a nation’s overall health and development. The impact of weight gain during pregnancy on short-term and long-term health outcomes underscores its significance in comprehensive pregnancy health management [ 1 , 2 , 3 , 4 ]. The findings, based on existing research evidence, suggested that excessive gestational weight gain (GWG) could lead to cesarean section, maternal weight retention, large-for-gestational-age (LGA) infants, gestational hypertension, preeclampsia, and gestational diabetes mellitus (GDM).…”
Section: Introductionmentioning
confidence: 99%
“…Several researchers have attempted to determine the factors that are linked to a successful Vaginal Birth after Caesarean (VBAC). These factors include: having had a previous vaginal birth before a caesarean section (CS), having had a previous successful VBAC, having a normal body mass index before pregnancy, having a higher bishop score and a favourable cervical status upon admission, being of a younger maternal age, and having a non-recurring indication for a previous CS such as fetal malpresentation and a non-reassuring fetal heart pattern (34-38) (Eloranta et al, 2023;Girma et al, 2021;Li et al, 2019;Tesfahun et al, 2023). Presently, apprehensions regarding the potential hazards of TOLAC have resulted in only a handful of obstetricians and expectant mothers who are prepared to undergo TOLAC voluntarily.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to pre-pregnant overweight and obesity, gestational weight gain (GWG) above the recommendation of Institute of Medicine (IOM, 7.0-11.5 kg for overweight and 5.0-9.0 kg for obesity) can also increase the risk of CS. Eloranta AM et al found that excessive GWG increased the risk of intrapartum caesarean section among normal weight (adjusted odds ratio [aOR] 1.46, 95%CI 1.23–1.73) and overweight women (aOR 1.291, 95%CI 1.04–1.60) [ 9 ]. In the Chinese population, the aOR of CS was 1.42 (95% CI 1.06–1.88) for excessive GWG [ 10 ].…”
Section: Introductionmentioning
confidence: 99%